Associations between maternal personality dysfunction and emotion suppression and adolescent emotion suppression - Jennifer J. Phillips; Cynthia L. Smith; Martha Ann Bell (Borderline Personality Disorder and Emotion Dysregulation)
Abstract Background Adaptive strategies of emotion regulation are important for adolescents, as maladaptive strategies of such can manifest as psychopathology that is sometimes severe. Individual biological characteristics and influences from peers have been shown to have an effect on the development of emotion regulation strategies in adolescents. Maternal factors, however, have received less attention in this age group regarding how they might predict emotion regulation in adolescents. Given that prior work has demonstrated that certain maternal factors, like emotion regulation and personality, play a crucial role in the development of emotion regulation strategies in early childhood, we sought to examine these associations in adolescents in our current study. Methods Adolescents and their mothers (n = 123) both self-reported data on their own emotion regulation, and mothers also self-reported data on their own personality dysfunction. We operationalized maternal and adolescent emotion regulation as emotion suppression, a maladaptive emotion regulation strategy that is commonly used by adolescents. Results Our data demonstrated that both maternal emotion suppression and interpersonal personality dysfunction were positively associated with adolescent emotion suppression. No associations among maternal intrapersonal personality functioning and adolescent emotion suppression were detected. Conclusions Maternal personality dysfunction and emotion suppression both independently predicted adolescent emotion suppression use. These results support the idea that maternal characteristics play a role in shaping emotion regulation in adolescence.